THE INVESTIGATION OF SOIL MAGNETIC PROPERTIES IN THE EASTERN FOREST-STEPPE AGROGEOPHYSICAL STATION - MENSHOV, O.; SUKHORADA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The magnetic properties of the soil cover of The East Forrest-Stepp agrogeophysical station are considered. The distribution of the magnetic susceptibility, natural remanent magnitization, summary and effective magnetization in the soil genetical horizons and in connection with geomorphological situations are described.